Changing of the guards: Detrital zircon provenance tracking sedimentological reorganization of a post-Gondwanan rift margin - Barham, Milo; Kirkland, Chris (WILEY, 2019)
© 2019 The Authors. Basin Research © 2019 John Wiley & Sons Ltd, European Association of Geoscientists & Engineers and International Association of Sedimentologists